Exploring Managers’ Perspective on Factors Affecting Generation Y Retention - Dideana, Thompson; Agatha Lamentan, Muda (Universiti Malaysia Sarawak, 2021)
The study explores factors behind Generation Y employees' retention from the perspective of managers in a financial services sector. A qualitative method was employed, by interviewing eight managers as informants. The results show ten factors affecting Generation Y employees’ retention are compensation and pay, personal development, job security, job satisfaction, work-life balance, reward and recognition, training, leadership, relationship and communication, and work environment. Seven main challenges to retain Generation Y employees identified are loyalty, their love for a challenging job, communication, strategy, working style, satisfaction, and traits. The study discusses implications and suggestions for organisational level strategies to retain Generation Y employees.